Observational evidence of electron pitch angle scattering driven by ECH waves. Issue 22 (24th November 2014) - Kurita, Satoshi; Miyoshi, Yoshizumi; Cully, Christopher M.; Angelopoulos, Vassilis; Contel, Olivier Le; Hikishima, Mitsuru; Misawa, Hiroaki
Abstract Using the plasma wave and electron data obtained from Time History of Events and Macroscale Interactions during Substorms, we show a signature of electron pitch angle scattering driven by Electrostatic Cyclotron Harmonic (ECH) waves in the velocity distribution function (VDF). The diffusion curve of whistler mode waves is used as a proxy to identify changes in VDFs due to wave‐particle interactions. We confirm that the shape of the VDF well agrees with the diffusion curve of whistler mode waves when whistler mode chorus alone is active. On the other hand, we find that the shape of the VDF deviates from the diffusion curves at low pitch angles when ECH waves are active following the inactivation of chorus waves. The result is observational support for electron pitch angle scattering caused by ECH waves and suggests that ECH waves can contribute to generation of diffuse auroras.